2013
DOI: 10.1186/1742-4933-10-43
|View full text |Cite
|
Sign up to set email alerts
|

Association of a common TLR-6 polymorphism with coronary artery disease – implications for healthy ageing?

Abstract: BackgroundThe pro-inflammatory status of the elderly triggers most of the age-related diseases such as cancer and atherosclerosis. Atherosclerosis, the leading cause world wide of morbidity and death, is an inflammatory disease influenced by life-style and genetic host factors. Stimuli such as oxLDL or microbial ligands have been proposed to trigger inflammation leading to atherosclerosis. It has recently been shown that oxLDL activates immune cells via the Toll-like receptor (TLR) 4/6 complex. Several common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 50 publications
0
23
0
9
Order By: Relevance
“…It was found that homozygosity for the TLR6 Pro249Ser genotype protects from atherosclerosis, and a significant increase in the frequency of the Pro249Ser SNP with age was observed. 22 Hamann et al speculate that this TLR6 variant may confer its beneficial effects by decreasing inflamm-ageing during older age. 22 Little is known about the role of TLR SNPs in the pathogenesis of CMV infection in humans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that homozygosity for the TLR6 Pro249Ser genotype protects from atherosclerosis, and a significant increase in the frequency of the Pro249Ser SNP with age was observed. 22 Hamann et al speculate that this TLR6 variant may confer its beneficial effects by decreasing inflamm-ageing during older age. 22 Little is known about the role of TLR SNPs in the pathogenesis of CMV infection in humans.…”
Section: Discussionmentioning
confidence: 99%
“…22 Hamann et al speculate that this TLR6 variant may confer its beneficial effects by decreasing inflamm-ageing during older age. 22 Little is known about the role of TLR SNPs in the pathogenesis of CMV infection in humans. The clinical relevance of TLR2 and TLR4 polymorphism has previously been suggested only in immunocompromised populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The heterodimeric complex of toll like receptors (TLR) 2 and TLR6 (TLR2-TLR6) is central to sensing bacterial di- and tri-acylated peptides 35,36 . A recently described SNP in the Tlr6 gene has been linked to left ventricular wall thickening and markers of inflammation 37,38 , and Tlr2 −/− mice have strikingly reduced atherosclerosis, especially when challenged with synthetic TLR2 agonists 36 . Furthermore, transplantation of bone marrow from mice lacking the double-strand DNA receptor TLR3 into LDLr −/− , which is a commonly used mouse model of atherosclerosis driven by elevated low density lipoprotein cholesterol levels mice results in reduced atherosclerosis burden 39 .…”
Section: Microorganism-associated Molecular Patternsmentioning
confidence: 99%
“…Сам ген TLR6 локализован на коротком плече четвертой хромосомы (4р13). При наличии вариантного аллеля по rs5743810 гена TLR6 (замена серина [Ser] пролином [Pro] в позиции 249), что приводит к снижению воспалительного ответа [25,57].…”
Section: Introductionunclassified